Mechanisation in the Periphery: The Experience of Chilean Agriculture, C. 1850-90 - Robles-Ortiz, C (Cambridge University Press, 2018)
This article examines mechanisation during the period of export-led growth in Chilean agriculture, c. 1850-90. According to conventional wisdom, since labour was cheap, landowners did not modernise their haciendas. The introduction of machinery was late and superficial; the large estate remained backward and inefficient. This view is flawed by lack of quantitative evidence and a narrow approach. Using imports and stocks data, and case material from the National Agricultural Society s bulletin, the article presents an alternative interpretation. The development of the market for agricultural equipment involved a fruitful exchange of technical expertise between the foreign importing companies and local landowners and experts. Mechanisation solved labour supply bottlenecks, and developed primarily on harvest tasks, above all the threshing of wheat. The scale and pattern of mechanisation were consistent with the development of this process in other countries older agricultures. The area mechanically harvested was much larger than previously estimated. Mechanisation was a significant transformation in the agricultural sector. Copyright © Cambridge University Press 2018.